Effect of different levels of Ipomoea batatas flour inclusion on the ruminal pH of sheep in metabolic cages - Edgard Gonçalves Malaguez; Maurício Cardozo Machado; Kauani Borges Cardoso; Marcio Nunes Corrêa; Cassio Cassal Brauner; Antônio Amaral Barbosa; Gilberto Vilmar Kozloski; Francisco Augusto Burkert Del Pino (Acta Scientiarum. Animal Sciences, 2021)
The accumulation of industrial by-products increases the use of sweet potato waste for ruminants, but ruminal pH characteristics are still not well known. The objective was to assess the fluctuation of ruminal pH in sheep supplemented with different levels of sweet potato flour inclusion in their diet. Four rumen-fistulated sheep were used; they were fed a diet based on ryegrass haylage (Lolium multiflorum) and sweet potato flour (Ipomoea batatas), provided according to the level of inclusion in the total diet (0, 0.5, 1.0 and 1.5%). Approximately 80 ml of ruminal fluid was collected for reading on a bench pH meter. Statistical data analysis was run on Statistical Analysis System (SAS Institute INC. Cary, NC, USA), and statistical difference was considered for p < 0.05. The animals that received 1.5% of sweet potato flour in their diet presented acid rumen pH; the 1.0% group presented rumen pH acidification in the first 6 hours after feeding, and the 0.5% level of inclusion did not change the rumen environment. It is concluded that the inclusion of 0.5% sweet potato flour in sheep diet proved to be an efficient energy supplementation strategy.